In-situ strengthening of a high strength low alloy steel during Wire and Arc Additive Manufacturing (WAAM) - Rodrigues, Tiago A.; Duarte, V. R.; Tomás, D.; Avila, Julian A. [UNESP]; Escobar, J. D.; Rossinyol, Emma; Schell, N.; Santos, Telmo G.; Oliveira, J. P. (Elsevier, 2020)
In this work, SiC particles were added to the molten pool during WAAM of a high strength low alloy steel. The introduction of these high melting point particles promoted grain refinement, and the precipitation of Fe3C due to SiC dissociation. The microstructural evolution was studied by optical and electron microscopy techniques and high energy synchrotron X-ray diffraction. Additionally, mechanical testing and hardness profiles were obtained for the SiC-containing and SiC-free parts. An improvement in the mechanical strength of the SiC-added WAAM parts was observed, which was attributed to the refined grain structure and finely dispersed Fe3C.
Keywords: HSLA steel; Inoculants; Mechanical testing; SiC; Synchrotron X-ray diffraction; Wire and Arc Additive Manufacturing